Single-pulse Morphology of PSR J1935+1616 (B1933+16) Based on Archival Data from FAST - R. W. Tian; R. S. Zhao; Marilyn Cruces; H. Liu; D. Li; P. Wang; C. H. Niu; Biping Gong; C. C. Miao; X. Zhu; H. W. Xu; W. L. Li; et al. (The Astrophysical Journal)
We utilized archive data from the Five-hundred-meter Aperture Spherical Radio Telescope (FAST) to analyze the single-pulse profile morphology of PSR J1935+1616 (B1933+16). The results show that PSR J1935+1616 exhibits significant micropulses as well as various changes in single-pulse profile morphology. In the FAST archive data, a total of 969 single pulses with microstructure were identified, accounting for 9.69% of the total pulse sample, with characteristic widths of $127.6{3}_{-46.25}^{+70.74}$ μ s. About half of these pulses display quasiperiodic micropulses, with a periodicity of 231.77 ± 9.90 μ s. Among the 520 single pulses with quasiperiodic microstructure, 208 also exhibit quasiperiodicity in circular polarization, with a characteristic period of $244.7{0}_{-21.05}^{+45.66}\,μ \,\rm{s}\,$ . The micropulse characteristic width in circular polarization is 106.52 ± 46.14 μ s. Compared to normal pulses, the relative energy ( E /< E >) of a single pulse with microstructure follows a double-Gaussian distribution, while those of normal pulses follow a single-Gaussian distribution. Based on the intensity of the leading and trailing components in the single-pulse profile morphology of PSR J1935+1616, we classified the pulses into four morphological modes (A, B, C, and D). The relative energy distribution of pulses in Mode A is significantly different from the others, following a double-Gaussian distribution, while the relative energy distributions in Modes B, C, and D follow a single-Gaussian distribution. Our study also suggests a possible correlation between micropulses and single-pulse profile morphology. Single pulses with micropulses are most likely to occur in Mode A, while their occurrence is least likely in Mode D.